Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/09593985.2018.1482980
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the recovery trajectories of knee range of motion for one year after total knee replacement

Abstract: The results showed that the maximum gains in knee ROM should be expected within the first 12 weeks with small changes occurring up to 26 weeks after TKR. In addition, age and presurgery knee ROM are associated with the gains in knee ROM and should be factored into the estimation of expected knee ROM at a given follow-up interval after TKR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…47 It has been shown that mean flexion of 114 o can be achieved by three months post-operatively and further small increases can occur between three months and 12 months post-operatively. 49,50 In another study, the mean range of motion was 114 o in patients who were able to kneel and 110 o in patients unable to kneel, 47 highlighting that flexion is not an important cause of kneeling problems. However, flexion is an important outcome after TKR and innovations in implant design which aim to increase flexion have been evaluated.…”
Section: Aetiologymentioning
confidence: 98%
“…47 It has been shown that mean flexion of 114 o can be achieved by three months post-operatively and further small increases can occur between three months and 12 months post-operatively. 49,50 In another study, the mean range of motion was 114 o in patients who were able to kneel and 110 o in patients unable to kneel, 47 highlighting that flexion is not an important cause of kneeling problems. However, flexion is an important outcome after TKR and innovations in implant design which aim to increase flexion have been evaluated.…”
Section: Aetiologymentioning
confidence: 98%
“…Active knee flexion ROM was measured by two orthopedic doctors before surgery (baseline), at the end of inpatient stay, and at outpatient follow-up admissions. After inpatient discharge, each patient was asked to admit outpatient follow-up clinic one to two times per month until a full recovery of knee flexion ROM (i.e., 130 to 135 degrees [62,63]) was achieved. In addition, the outpatient follow up for each patient was continued for a time period as long as nine months to ensure the maximum gains in knee ROM after TKR, despite recovery of knee flexion ROM reaching a peak at 3−6 months after TKR [13,62].…”
Section: Measurement and Follow Up Of Knee Flexion Range Of Motionmentioning
confidence: 99%
“…Additionally, concomitant factors like age and pre-surgery knee ROM are associated with the gains in knee ROM. They should also be factored into the approximation of expected knee ROM at a given follow-up interval after TKA [26]. Balance and proprioception improved as compared to pre-operative levels at 1year post operatively [27].…”
mentioning
confidence: 99%